2018
DOI: 10.1103/physrevb.97.214209
|View full text |Cite
|
Sign up to set email alerts
|

Spinful Aubry-André model in a magnetic field: Delocalization facilitated by a weak spin-orbit coupling

Abstract: We have incorporated spin-orbit coupling into the Aubry-André model of tight-binding electron motion in the presence of periodic potential with a period incommensurate with lattice constant. This model is known to exhibit an insulator-metal transition upon increasing the hopping amplitude. Without external magnetic field, spin-orbit coupling leads to a simple renormalization of the hopping amplitude. However, when the degeneracy of the on-site energies is lifted by an external magnetic field, the interplay of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Finally, in this paragraph we want to briefly summarize some of the reported predictions of the Aubry-André model. These include spin-orbit coupling effects [41], closed expressions for the energy separating localized and non-localized states [42] and coexistence of localized and extended states in interacting quasiperiodic systems [43] among others. At the many-body level, localization of the ground state is established rigorously in the weakly interacting regime for both repulsive and attractive interactions [44] and many-body localization versus thermalization and onset of equilibrium [45], which can have implications for quantum devices and quantum computation.…”
Section: Final Remarksmentioning
confidence: 99%
“…Finally, in this paragraph we want to briefly summarize some of the reported predictions of the Aubry-André model. These include spin-orbit coupling effects [41], closed expressions for the energy separating localized and non-localized states [42] and coexistence of localized and extended states in interacting quasiperiodic systems [43] among others. At the many-body level, localization of the ground state is established rigorously in the weakly interacting regime for both repulsive and attractive interactions [44] and many-body localization versus thermalization and onset of equilibrium [45], which can have implications for quantum devices and quantum computation.…”
Section: Final Remarksmentioning
confidence: 99%
“…Concerning possible applications of this method, we highlight some of them: (i) as the groundwork of future studies in commensurate Aubry-André/Harper models [12][13][14][15][16][17][18][19][20][21][22][23], (ii) in the topological characterization of ISSH m models, such as the ISSH 3 [15,18,[44][45][46][47][48], ISSH 4 [41,[49][50][51][52][53] and ISSH 6 [50,54] models, (iii) in studies on quantum state transfer across more complex ISSH m models [55][56][57][58], and (iv) in simplifying the calculation of expectation values of arbitrary operators or interacting matrix elements in many-body problems built on these models [10].…”
Section: Discussionmentioning
confidence: 99%
“…, m and T defined in (56). In order to express W i n in terms of Chebyshev polynomials U n , we compute W i 1 = T N −1 χ i 1 and W i 2 = T N −2 χ i 2 to find, using the same inductive reasoning followed in (21)(22)(23),…”
Section: Non-integer Number Of Unit Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in general the long-range interactions in 1D systems prevent full Anderson localisation [28,29], and recent work has shown that homogeneous long-range coupling [30] or coupling to cavities [31] can significantly alter 1D responses to disorder in ways beyond the scope of this paper. Recent years have also seen broad interest in the transient effects of dephasing on quantum diffusion, such as stochastic resonance, and many-body localisation, especially focussed on the quasiperiodic Aubry-André model [12,[32][33][34][35][36][37], as well as quantum chaotic systems Coloured areas show ± one standard deviation, each point is averaged from 100 configurations of disorder. An ordered ( ) and disordered ( ) point are highlighted, and their eigenspectra shown in the centre and right panels, respectively.…”
Section: Figurementioning
confidence: 99%